Characterisation of carbon paste electrodes bulk-modified with surfactants for measurements in nonaqueous media. (1st April 2022) - Jashari, Granit; Švancara, Ivan; Sýs, Milan
Highlights: The first detailed characterization of carbon paste electrodes bulk-modified with surfactant. Systematic optimisation of the carbon paste composition for nonaqueous media. Studies on relations between the carbonaceous material, binder, and the type of surfactant. Kinetic investigation of ferrocenium/ferrocene and quinone/hydroquinone redox couples. Abstract: This article deals with carbon paste electrodes bulk-modified with surfactants for measurements in pure organic solvents where common carbon paste-based mixtures undergo disintegration. The electrodes of interest were prepared by mixing of selected carbon materials (namely: two types of graphite powder, glassy carbon powder, raw shungite powder, and multi-wall carbon nanotubes, with various binders (mineral oil, silicone oil, paraffin wax, vaseline, atactic polypropylene, and tricresyl phosphate), together with surfactants of choice (sodium dodecyl sulfate, cetylpyridinium chloride, benzethonium chloride, cetyltrimethylammonium bromide, didodecyldimethylammonium bromide, Triton X-100, and 1, 3‒didecyl‒2‒methylimidazolium chloride). The corresponding studies were focused on the optimal composition of the individual pastes and their characterisation in organic solvents, when using cyclic voltammetry with model redox pairs (ferrocenium/ferrocene and quinone/hydroquinone). The results obtained suggest one that amount of the individual components depends predominantly on the type of carbon used. Key factors for selection of the proper surfactant are its polarity, chemical inertness, and electrochemical inactivity. For comparison, glassy carbon disc electrode was also used. Graphical abstract: Image, graphical abstract